O gestor do lazer dos clubes esportivos, sociais e recreativos de Belo Horizonte: uma visão da formação e atuação profissional - Taciana Soares de Oliveira (2019)
Sports / social / recreational clubs, understood as leisure spaces, are important establishments for the promotion of social, cultural and sports activities. They have very peculiar characteristics that differ from any other segments in the leisure field. They are constituted in a complex and dynamic network of sociability, by the numerous relationships with the various institutions of society and by their various forms of sociability of people's daily lives. Thus, the perception of professionals who work with leisure management in the club environment is interesting to understand what are the necessary knowledge for a professional performance that involves a set of tasks that seek to ensure the politics in practice. In this context, this research aimed to know and analyze the social and professional profile of leisure managers working in sports / social / recreational clubs in Belo Horizonte. In addition, it sought to identify and discuss the knowledge understood as important for this professional performance, identify how and where the professionals acquired such knowledge, address the difficulties for professional performance, and describe the leisure understanding of these professionals. As a methodology, I used the qualitative approach, which involved the combination of bibliographic and field research. The bibliographic research was guided by research on the clubs, contextualizing this space and its dialogue between associations and leisure, as well as references on the formation and professional performance in leisure management. The field research was conducted through seven semi-structured interviews with managers who are responsible for supervising, managing, organizing, and promoting sports, recreational and leisure activities. For the treatment of the data the technique of content analysis was used. As a result of the analysis, I noticed that managers have different initial education trajectories and when they are approached about the specific knowledge for professional performance, they relate learning with practice and insertion in the job market. Thus, they emphasize that there are gaps in their training that are directly related to the knowledge inherent in management. In addition, I verified that the interviewed managers have different understandings about the leisure phenomenon. In this sense, we can conclude that the profile for acting with leisure management in sports / social / recreational clubs is formed by professionals from different areas of training, who acquired the specific knowledge to act during professional experiences and, finally, understanding of managementrelated content.